Urban agglomeration: integrity or discreteness? - Bondarenko, Igor (project baikal, 2025)
A critical examination of the concept of “agglomeration”, which was borrowed by urban planning from the field of metallurgy, calls for its rethinking and filling with more adequate professional content that meets the interests of forming a community of independent cities that preserve their borders, natural surroundings, architectural face, historical and cultural identity. The thesis is substantiated that, unlike individual cities, agglomerations should not strive to achieve organic integrity. They should remain discrete, based on the principle of “additive” summation of the elements of an open system.